ANALISIS EFISIENSI PENENTUAN PORTOFOLIO SAHAM PERUSAHAAN MANUFAKTUR DI PT. BURSA EFEK INDONESIA (BEI) - Pangaribuan, Jonner (UNIKA Santo Thomas, 2012)
companies, as well as the influence of optimal portfolios and efficient manufacturing companies on stock returns in IDX. Benefits gained for investors itself is as an input to invest in stocks is optimal. The population in this study are all companies listed on the Stock Exchange, and the samples used are as many as 152 shares of manufacturing companies are divided into two portfolios based on market capitalization and value of corporate assets. Data collection techniques used by technical documentation, that the financial statements of companies that have previously run for two years ie from 2002 to 2003 observations. The data analysis technique used is multiple linear regression. Based on the results of the regression can be concluded that the higher the premium market significantly increases the risk of a stock portfolio of manufacturing companies. Regression coefficient for the independent variable on the dependent variable ERM portfolio return has a positive influence on the company. From the observations made, the optimal portfolio is the portfolio to be done based on the value of assets, particularly as it offers a great asset portfolio return of 55 percent with a 100 percent risk. Obviously the determination of the optimal portfolio for an investor to do and are applied in the efficient frontier curve is in accordance with the preferences of the investor returns and are willing to bear the risk. Therefore, investors should consider the investment shares of SBI level, analyzing the stock price and the expected return on a portfolio that is offered, as well as selecting a portfolio of shares in accordance with the preferences of the investor.